(untitled) (LACCEI, 2024)
The objective of this study was to determine if social responsibility influences the purchasing decision of millennial consumers in the cosmetics industry, metropolitan Lima 2021. This research is pure, with a quantitative approach, a causal correlational level, and its design is non-experimental. cross type. The study population consisted of 1,673.4 millennial women from metropolitan Lima, in an age range of 21 to 40 years, the nonprobabilistic sample was used for convenience, since 180 women from the population were selected for utility. The technique applied was the survey and the instrument used was the questionnaire, which was validated by expert teachers and submitted to the Aiken V test, resulting applicable and for reliability, Cronbach’s Alpha coefficient was used, whose result was 0.977, which meant a high statistical reliability. Finally, it was determined that social responsibility significantly influences the purchasing decision of millennial consumers in the cosmetics industry, metropolitan Lima 2021, demonstrated through a Chi-Square test with a value of 35,882 and an asymptotic significance level of 0.000, which clearly indicates that the development of social responsibility significantly influences the purchase decision.